UNIVERSITY-ENTERPRISES COOPERATION AS A DETERMINANT OF INNOVATION - Zbigniew Zontek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
The aim of this article is to identify the role of cooperation between enterprises and universities in creating innovative solutions. This form of cooperation still faces several barriers, connected with the mismatch of both cooperation sides and because of functioning stereotypes. The results of research presented in this study indicate that it is necessary to stimulate the creation of new mechanisms of cooperation between these two sectors, therefor the new model of cooperation is presented.